Nonsurgical Periodontal Therapy Impacts Salivary and Serum Bone Turnover Markers in Periodontitis - Javed, Faraha; Zia, Afaf; Khan, Asad Ullah; Bey, Afsha; Hakim, Seema; Ateeq, Hira; Yusufi, Faiz Noor Khan; Salati, Nasir (European Dental Research and Biomaterials Journal, 2024)
Objectives To assess nonsurgical periodontal therapy's (NSPT's) effect on bone turnover markers (BTMs) in periodontitis patients and compare the efficacy of saliva and serum samples in evaluating periodontal health.Materials and Methods Sixty-five females aged 18 to 45 years were divided into control (n = 20) and test (n = 45) groups. Periodontitis patients underwent NSPT. Full mouth clinical periodontal parameters and salivary/serum BTMs (C-terminal telopeptides of type I collagen [CTX], bone-specific alkaline phosphatase [BALP], osteoprotegerin [OPG]) were recorded at baseline, 3 weeks, and 3 months post-NSPT.Statistical Analysis The study measured test group readings at three points: baseline, 3 weeks, and 3 months after NSPT. Normality was assessed using the Shapiro–Wilk test, showing a nonnormal distribution (p < 0.05). To test for significance among groups, the Kruskal–Wallis test was applied. The Friedman test, along with pairwise comparisons, was used to compare test group readings across time points. A 5% significance level was maintained. Pearson correlation measured relationships between the control and test groups and within the test group at different intervals. Multiple linear regression was conducted across time points, with plaque index (PI), gingival index (GI), probing pocket depth (PPD), and clinical attachment level (CAL) set as dependent variables, and salivary and serum BALP, CTX, and OPG as independent variables. All analyses were performed using IBM SPSS version 20 and R version 3.5.2.Results Following NSPT, significant changes were observed in all measured salivary/serum BTMs except serum BALP (p > 0.05). No significant differences noted between BTM measurements taken at 3 weeks and 3 months post-NSPT (p > 0.05). Correlations between BTMs and periodontal measurements were weak to moderate after NSPT. A multiple linear regression model explained 46.7% of the total variability for PI, 50.1% for PPD, 54.1% for CAL, and 29.3% for GI signifying association with BTMs among groups.Conclusion NSPT results in significant changes in salivary/serum BTMs. Following NSPT, BTMs show associations with periodontal parameters, highlighting modulation of host responses. BTMs in salivary/serum samples effectively reflected periodontal health and disease status and improvements after therapy.
Keywords: bone turnover markers; periodontal disease; nonsurgical periodontal therapy; saliva; serum